2003
DOI: 10.1121/1.4780911
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for calibrating multibeam sonar

Abstract: Development of protocols for calibrating multibeam sonar by means of the standard-target method is documented. Particular systems used in the development work included three that provide the water-column signals, namely the SIMRAD SM2000/90-and 200-kHz sonars and RESON SeaBat 8101 sonar, with operating frequency of 240 kHz. Two facilities were instrumented specifically for the work: a sea well at the Woods Hole Oceanographic Institution and a large, indoor freshwater tank at the University of New Hampshire. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 13 publications
0
35
0
4
Order By: Relevance
“…Multibeam, omnidirectional sonar allowed dynamic observations and was used to display reactions of schools to predation (Misund, 1993;Nøttestad and Axelsen, 1999;Brehmer, 2004). Recently, new acoustic instrumentation has allowed better description of school internal structures in 2D and 3D Mayer et al, 2002;Foote et al, 2005; see Reid, 2000, for a synthesis), and their evolution through time (Misund and Coetzee, 2000;Axelsen et al, 2001;Misund et al, 2005). Applying such tools to tropical clupeids, it has been shown that in many cases, a school's external morphology is liable to vary greatly while the internal structure remains unchanged (Gerlotto et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Multibeam, omnidirectional sonar allowed dynamic observations and was used to display reactions of schools to predation (Misund, 1993;Nøttestad and Axelsen, 1999;Brehmer, 2004). Recently, new acoustic instrumentation has allowed better description of school internal structures in 2D and 3D Mayer et al, 2002;Foote et al, 2005; see Reid, 2000, for a synthesis), and their evolution through time (Misund and Coetzee, 2000;Axelsen et al, 2001;Misund et al, 2005). Applying such tools to tropical clupeids, it has been shown that in many cases, a school's external morphology is liable to vary greatly while the internal structure remains unchanged (Gerlotto et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…For both sonars, the third dimension was obtained from the succession of pings along the vessel course. Both sonars were manufacturer-calibrated, and checked before the survey using known targets, but they were not calibrated in situ due to the difficulty of carrying out the procedure recommended by Foote et al (2005) and Melvin et al (2003) in the field. The acoustic survey was conducted during daylight on September 23, 2008 along transects of the northern part of the lake, using a protocol described in Guillard et al (2006a) designed to optimize the probability of encountering fish schools during the experiment.…”
Section: Multibeam Sonars (Mbs) and Acoustic Surveysmentioning
confidence: 99%
“…1 [6,14]. A 60-mm-diameter sphere of aluminum was used as the standard target, its target strength having been determined by intercalibration against another standard target whose material properties were better known.…”
Section: Present Limitationsmentioning
confidence: 99%
“…Applications have included, for example, observation of fish behavior due to passage of acoustic surveying vessels or pelagic trawls, measurement of swimming speed, study of predator-prey interactions, measurement of bubble populations and particulate concentrations near hydrothermal vents, with references given in [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation